On the approximate functional equation of Hecke’s Z-functions - Bulota, K. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: К. Булота. О приближенном функциональном уравнении Z-функций Гекке K. Bulota. Apie Hekės Z-funkcijų artutinę funkcionalinę lygtį